Dielectric and energy storage properties of (La, Li)x[(Bi, Na)BaSrCa]1-xTiO3 high-entropy perovskite ceramics. Issue 17 (1st September 2022) - Zhou, Chenhe; Zhang, Xiaoyan; Li, Shuning; Yan, Jinhua; Qi, Xiwei
Abstract: A series of single-phase (La0.5 Li0.5 ) x [(Bi0.5 Na0.5 )0.25 Ba0.25 Sr0.25 Ca0.25 ]1- x TiO3 high-entropy perovskite ceramics were designed and successfully synthesized via conventional solid state reaction method. The results of dielectric properties indicate that all samples in different proportions exhibit excellent frequency stability at a wide frequency range (10 2 –10 6  Hz) and quintessential relaxation phenomenon. An optimal dielectric constant ( ε r  = 920) with low dielectric loss (tanδ = 0.015) was achieved for x  = 0.20, which is represented as equimolar high-entropy ceramic. It can be demonstrated that an amazing energy storage efficiency of 95.3% and a discharge density of 1.23 × 10 −2  J/cm 3 can be simultaneously achieved in x  = 0.24 ceramics. Furthermore, it is confirmed by X-ray photoelectron spectroscopy that the charge compensation mechanism and the oxygen vacancies synergistically cause more Ti 4+ to be reduced, which rationalizes the elevated dielectric properties. We believe that entropy engineering is a credible strategy for tailoring material properties.